KEY COMPONENTS OF TECHNICAL PREPARATION IN TABLE TENNIS (Web of Teachers: Inderscience Research, 2024)
Present article is devoted to the main key components of technical preparation in table tennis. All components have been given clearly by the table. Technical preparation focuses on developing the fundamental skills and techniques that enable players to execute strokes, movements, and strategies effectively during matches.